SOSIALISASI TEKNOLOGI WEBSOCKET UNTUK PENGELOLAAN TIKET EVENT DI GEDUNG SERBAGUNA UNILAM DAN KEGIATAN KAMPUS SECARA EFISIEN - Rachmat Nurcahyo; Syaiful Bachri; Ahmad Adnan (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
This Community Service Program (PKM) aims to introduce WebSocket technology as a digital solution for ticket management at the UNILAM Multipurpose Hall. The activity addresses challenges commonly found in manual ticketing systems, such as long queues, data inaccuracies, and operational inefficiencies. Through educational and demonstrative approaches, participants were introduced to the concept of WebSocket’s full-duplex communication and its capability to update ticket status in real time. The activity received enthusiastic responses from students, student organization leaders, event committees, and campus facility staff. A prototype application demonstrated the ease of ticket validation, instant notifications, and efficient participant data visualization. This initiative also opened opportunities for further development of comprehensive campus service digitalization. WebSocket proved to be an effective technology to enhance efficiency, transparency, and user experience in campus event management.